Henning Høirup: Frederik Lange Grundtvig - Albeck, Gustav (Grundtvig-studier, 1957)
Frederik Lange Grundtvig. By Henning Høirup, in collaboration with M. F. Blichfeld, Inger M. Boberg, and Hans E. Eriksen. By Gustav Albeck. It is more than a mere work of piety that Dean Høirup has performed in publishing this comprehensive book about Grundtvig’s youngest son. It appeared on the occasion of the centenary of Frederik Lange Grundtvig’s birth, but it is something other and more than a tribute to his memory. Dr. Høirup has taken charge of its publication and has written the greater part of the text, but has supplimented his own presentation of the subject with contributions from other writers. Thus the Rev. M. F. Blichfeld, who was a Danish clergyman in the U.S.A. and has now retired, has written Chapter V and VI of the book, which deal with F. L. Grundtvig’s activities in the Danish Church in America and his national work among Danish people there (1883—1900) and with his last tragic years (1900—1903), while Dr. Inger M. Boberg (who has since died) writes, with specialist knowledge and not without admiration, about F. L. Grundtvig’s comprehensive and original contribution as a collector of folk traditions. But the most important part of the book is Dr. Høirup’s description — full of understanding and insight — of F. L. Grundtvig’s childhood and youth, his literary work in America, partly as a poet for the Danish settlers in “the country where the nations gather”, partly as editor and publisher of » Sangbog for det danske Folk i Amerika« (“ Songbook for the Danish people in America”) — and finally as a theological author of treatises and studies of the Fathers of the Church. An enormous amount of work lies behind this well-informed and sympathetic biography — work based on both printed and unprinted sources. Dr. Høirup has had good help from many sides, not least from people who are still alive and who knew Frederik Lange Grundtvig and his work in America, especially his daughter, Mrs. Marie Lorange, Oslo. Of particular importance for research into N. F. S. Grundtvig’s life are the first chapters of the book, which paint a moving picture of the old father’s love for his little motherless son, and, at some decisive points, increase our knowledge concerning N. F. S. Grundtvig’s latest years. Frederik Lange Grundtvig’s life was tragic in many respects, because, in filial piety, he felt himself bound to his great father’s work and ideas and tried to preserve them and to realise them in practice in a land where the climate of thought was unfavourable to them — and in a period which was characterised by material progress more than by spiritual growth. But his destinity assumed dimensions which were worthy of the name which laid him under corresponding obligations, and it was not chance, but his own deeds and behaviour, which gave greatness to his all too short life.